Inference on a Structural Break in Trend with Fractionally Integrated Errors. (5th January 2016) - Chang, Seong Yeon; Perron, Pierre
Abstract : Perron and Zhu (2005) established the consistency, convergence rate and limiting distributions of parameter estimates in time trends with a change in slope with or without a concurrent level change for the cases with I(1) or I(0) errors. We extend their analysis to the general case of fractionally integrated errors with memory parameter d ∗ . Our results uncover interesting features; e.g., with a level shift allowed, the convergence rate for the break date estimate is the same for all d ∗ ∈(−0.5, 0.5). In other cases, it is decreasing as d ∗ increases. We also provide results about the so‐called spurious break issue.